Histone lactylation-boosted AURKB facilitates colorectal cancer progression by inhibiting HNRNPM-mediated PSAT1 mRNA degradation - Yuyi Li; Jinjin Peng; Di Wu; Qingxin Xie; Yichao Hou; Linjing Li; Xintian Zhang; Yu Liang; Jing Feng; Jiaqing Chen; Wangshuang Chen; Che Xu; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Aurora kinase B (AURKB), a key regulator of mitosis, is frequently upregulated in various malignancies, including colorectal cancer (CRC), and is associated with poor prognosis. However, the limited clinical efficacy of AURKB inhibitors suggests the existence of previously unrecognized oncogenic mechanisms that merit further investigation. Methods AURKB was prioritized through bioinformatic analysis, and its elevated expression in CRC was validated via single-cell RNA sequencing (scRNA-seq) and western blot. The transcriptional activation of AURKB was attributed to H3K18 lactylation, as confirmed by chromatin immunoprecipitation (ChIP)-qPCR. RNA sequencing (RNA-seq) and gene set enrichment analysis (GSEA) were conducted to pinpoint the downstream targets of AURKB. The role of the AURKB/phosphoserine aminotransferase 1 (PSAT1) axis in CRC was further studied using both in vitro and in vivo functional experiments. Mass spectrometry, co-immunoprecipitation (Co-IP), proximity ligation assay (PLA), RNA immunoprecipitation (RIP)-qPCR, and mRNA stability assays were employed to investigate the interplay and potential mechanisms involving AURKB, heterogeneous nuclear ribonucleoprotein M (HNRNPM), and PSAT1. Results AURKB was identified as an oncogene linked to advanced pathological staging and poor clinical outcomes in CRC. Its transcriptional upregulation was driven by H3K18 lactylation at its promoter. PSAT1 was further identified as a key downstream effector in AURKB-mediated CRC progression. Mechanistically, AURKB bound to HNRNPM and interfered with its interaction with PSAT1 mRNA, thereby suppressing HNRNPM-mediated mRNA degradation and ultimately increasing PSAT1 protein levels. Conclusion Our findings uncover a previously unappreciated, kinase-independent function of AURKB in CRC, redefining its therapeutic relevance beyond kinase inhibition. This highlights the need for broader targeting strategies, including PROTAC-mediated degradation of AURKB and pharmacological inhibition of the AURKB/PSAT1 axis, to fully harness its role in CRC treatment.